A fabric architecture towards block chain application using hyper ledger - Haseeb, Md; Raja Sekhar, K; V. Spandana, Y; Syam, M (International Journal of Engineering and Technology, 2018)
Block chain is a trust which can be best understood by the state machine replication, It is decentralized distributed ledger which is along all peers in the network connected through nodes over Internet. Every Node in the chain have equal stake and also the main factor is every node which have greater CPU cycles has a chance to operate node by spending those CPU cycles and also show Proof Of Work. Hence when the block chain is used in Business Models it loses its Private transactions and Confidential Contracts.Â Â